Infant feeding modalities addressed in two different ways in Eastern Uganda - Tumwine James K; Sommerfelt A Elisabeth; Shanmugam Rebecca; Engebretsen Ingunn MS; Tylleskär Thorkild (BMC, 2010)
Abstract Background Durations of exclusive breastfeeding (EBF) and predominant breastfeeding (PBF) from two different assessments, among the same mother-infant population, were investigated to determine the degree to which the assessments yielded overlapping results. Methods Thirty Ugandan mother-infant pairs were followed up weekly from birth to three months of age with weekly short-time feeding recall: the 24-hour recall asked prior to the 1-week recall. In addition, at week 6 and 12 dietary recalls since-birth were conducted. Variables for the duration of EBF and PBF were created from the short-time feeding recalls and the dietary recalls since-birth, respectively. Mean durations of EBF and PBF from the two assessments were compared with Kaplan Meier analysis at week 6 and 12. Reproducibility of dietary recall instruments was also assessed. Results At six weeks postpartum the mean durations of EBF were 0.50 weeks (95% CI: 0, 1.02) according to the weekly short-time recalls and 1.51 weeks (95% CI: 0.66, 2.35) according to the recall since-birth (Mantel-Cox test, p = 0.049). The mean durations of PBF were 4.07 weeks (95% CI: 3.38, 4.77) according to the frequent short-time recalls and 4.50 weeks (95% CI: 3.93, 5.07) according to the recall since-birth, (Mantel-Cox-test, p = 0.82). At twelve weeks the mean durations of EBF were 0.5 weeks (95% CI: 0, 1.1) according to the weekly short-time recalls and 1.4 weeks (95% CI: 0.1, 2.7) according to the recall since-birth (Mantel-Cox-test, p = 0.15). The mean durations of PBF were 5.2 weeks (95% CI: 3.9, 6.5) according to the weekly short-time recalls and 6.6 weeks (95% CI: 5.4, 7.8) according to recall since-birth (Mantel-Cox-test, p = 0.20). Reports of feeding categories and early feeding practices showed high reproducibility. Conclusion Comparing duration of EBF and PBF in this group of mother-infant pairs showed overlapping results from the weekly short-time assessment and the recall since-birth at twelve weeks, with the latter yielding slightly longer duration of the respective feeding modalities. The retrospective recall since-birth could be assessed as a cost-reducing tool compared to the frequent follow-up addressing duration of respective infant feeding modalities for evaluation of programmes promoting safer infant feeding practices. Trial registration The study was part of formative studies for the ongoing study PROMISE EBF registered at http://clinicaltrials.gov, NCT00397150.